Kombinasi Pijat Oksitosin Menggunakan Aromaterapi Pada Ibu Dengan Menyusui Tidak Efektif - Ningsih, Ratna; Rosnani, Rosnani; Jaya, Herawati; Marliza, Vivin Dwi (Jurusan Keperawatan, Poltekkes Kemenkes Palembang, 2024)
Background: Post partum mothers have their own impacts on mothers, including early initiation of breastfeeding (IMD) which is not fulfilled which results in problems with the mother's breastfeeding process. The ineffectiveness of post-partum breastfeeding makes it difficult for mothers to give breast milk to their babies. One effort that can be done is to do an oxytocin massage using lavender aromatherapy. Objective: To describe the implementation of oxytocin massage nursing using aromatherapy in post partum patients with ineffective breastfeeding. Method: The design of this case study is descriptive in the form of a case study with a nursing process approach consisting of assessment, nursing diagnosis, planning, evaluation and documentation. The case study subjects were 2 cases of post partum patients with ineffective breastfeeding at the Muhammadiyah Palembang Hospital in 2024. Results: The results of the case study after implementing oxytocin nursing using lavender aromatherapy showed that the results from patient 1 and patient 2 showed that breast milk supply increased. There is a significant relationship between breastfeeding and the ineffectiveness of giving oxytocin massage using lavender aromatherapy. Conclusion: Implementation of breastfeeding nursing is not effective. Giving oxytocin massage using lavender aromatherapy can be applied because it is effective in increasing breast milk production.